Method of non-contact remote determination of the current functional state of the athlete - Vadym Artemiev; Valeriy Druz; Andrii Yefremenko (Слобожанський науково-спортивний вісник, 2020)
Purpose: development of a non-contact method for monitoring the current functional state in the process of the direct implementation of professional activities. Materials & Methods: analysis of scientific and methodological literature; biomechanical analysis of kinematic, dynamic and static characteristics of motor activity; computer simulation of the dynamics of interaction of controlled indicators; methods of mathematical statistics. Results: based on the results, their analytical dependencies were determined, on the basis of which the corresponding mathematical models were built. They allow you to study the dynamics of the interdependence of controlled parameters in the expected modes of their interaction without the participation of the object of study. Conclusions: analytical patterns that describe the interdependence of the biomechanics of motor activity and mathematical models of reflection, as well as modern means of video recording and computer processing, provide an advantage for an effective assessment of the motor activity of an individual.